Serp-1 Promotes Corneal Wound Healing by Facilitating Re-epithelialization and Inhibiting Fibrosis and Angiogenesis - Ju, Brent; Guo, Owen; Benissan-Messan, Dathe Z.; Shawver, McKinley H.; Chen, Peng; Geng, Bingchuan; Wei, Siqi; Yaron, Jordan R.; Lucas, Alexandra R.; Zhu, Hua (Frontiers in Cardiovascular Medicine, 2021)
Purpose: Chemical corneal injuries carry a high morbidity and commonly lead to visual impairment. Here, we investigate the role of Serp-1, a serine protease inhibitor, in corneal wound healing. Methods: An alkaline-induced corneal injury was induced in 14 mice. Following injury, five mice received daily topical saline application while nine mice received Serp-1 100 μL topically combined with a daily subcutaneous injection of 100 ng/gram body weight of Serp-1. Corneal damage was monitored daily through fluorescein staining and imaging. Cross sectional corneal H&E staining were obtained. CD31 was used as marker for neovascularization. Results: Serp-1 facilitates corneal wound healing by reducing fibrosis and neovascularization while mitigating inflammatory cell infiltration with no noticeable harm related to its application. Conclusions: Serp-1 effectively mitigates inflammation, decreases fibrosis, and reduce neovascularization in a murine model of corneal injury without affecting other organs. Translational Relavence: Our study provides preclinical data for topical application of Serp-1 to treat corneal wounds.